Advancing soil biology research: Empowering European databases with ontological frameworks for enhanced data integration of soil biodiversity data - José F. Aldana-Martín; David J. Russell; Carlos A. Martínez-Muñoz; Christine Driller; Stephan Lesch; Ismael Navas-Delgado (Ecological Informatics)
Recognizing soil biodiversity’s critical role in soil quality and health has gained prominence in environmental policy and research. There is a pressing need to integrate taxonomic data with functional traits to understand the functional significance of soil biodiversity and its distribution across various environmental contexts. This long-term goal can only be achieved after comprehensive taxonomy ontologies are in place.Ontologies are a powerful tool to facilitate database interoperability, ensuring a seamless connection between diverse datasets. Adopting ontologies aligns with the FAIR principles, enhancing data discoverability, accessibility, and machine-readability. In biology, ontologies offer a robust framework for formalizing complex relationships between taxa, traits, and environments. Repositories like the OBO Foundry and NCBO BioPortal further promote the integration of controlled bioscientific vocabularies. However, careful selection of vocabulary is essential to ensure effective interoperability among ontologies, especially when dealing with closely related taxa.While databases like Edaphobase provide comprehensive taxonomic information for soil invertebrate animals, they lack specific ontologies for the underlying taxonomic structure. This research addresses this gap by proposing the EUdaphobase Taxonomy Ontology (EUTaxO) tailored to soil biology taxonomy. As Edaphobase is continuously updated to accommodate changes in taxonomic classifications, the related EUTaxO will require maintenance. This work presents an automated pipeline to synchronize the proposed ontology with Edaphobase’s classification.The integration of observational databases, such as Edaphobase, with domain-specific trait databases will enable the aggregation of species into functional or ecological groups based on traits. This integration, primarily reliant on taxonomic characteristics, will be critical in evaluating the spatio-temporal distribution of functional soil biodiversity across diverse habitats, soil types, climate zones, and land-use patterns.